Amperometric Detection of Nitrite Using Chitosan Protected Copper Phthalocyanine Sulfonate Functionalized Multiwalled Carbon Nanotube Modified GCE in Water Samples - Porchelvi, K.N.; Sudarvizhi, A.; P, K. (Asian Journal of Chemistry, 2013)
Nanocomposite of chitosan protected copper tetrasulfonated phthalocyanine (CuTsPc) functionalized multiwalled carbon nanotube was synthesized by mixing of a known quantity of CuTsPc dispersed chitosan solution in presence of MWCNT as pillar agent. The surface morphology was confirmed from FE-SEM, UV-VIS and FT-IR analysis. The electrochemical behaviour of the system was investigated in presence of a redox probe. The nanocomposite film modified GCE was utilized for the electrochemical detection of nitrite in different pH ranges. A calibration graph was constructed by plotting the concentration of nitrite against the peak current. The unknown concentrations of nitrite were determined from the calibration graph. The standard addition method was adopted to measure the unknown concentration of nitrite present in water samples.